(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
This article examines the psychological, social, and environmental factors that shape the personality formation of young adolescents aged 12–15. Drawing on developmental psychology and educational research, the study analyzes the influence of biological changes, cognitive growth, family dynamics, peer relationships, school environments, and digital media on adolescent identity development. Special attention is given to the challenges young adolescents face in balancing autonomy with social belonging, emotional regulation, and identity exploration. The article also discusses the role of supportive parenting, positive peer networks, and inclusive educational settings in fostering resilience, self-esteem, and healthy personality development. The findings underscore the need for an integrated approach involving parents, educators, and mental health professionals to help adolescents successfully navigate this critical developmental stage.